“HA FOLYÓVĺZ VOLNÉK ... (HAD I BEEN RUNNING WATER ...)”, EQUAL VOICES CHOIR, OP. 1, BY EDE TERÉNYI (1954) - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
In 2008 I published in the review Studia UBB Musica a biographical study, about the composer Ede Terényi. I had the following motto at the beginning of the study: “Had I been running water, / I would not know the trouble; / Among mountains and valleys, / Beautifully, I would flow slowly; / I would wash shores, / I would renew herbs, / To the thirsty birds, / I would offer water.” This is the text of a folk song, which was taken and processed by the composer Ede Terényi, in 1954, as a little choral musical work on three equal voices, a woman (or children) choir, that was inspired by the “Choral Works for Children’s and Female Voices” of Bartók. Retroactive, the composer, considers this little work as his really work op. 1. The present study aims to analyse this little work, which is very close to the composer’s soul.